Analysis of the Influence of TikTok Social Media Application Usage on Academic Achievement Among @Perkedel69 Followers - Sinaga, Victor; Aswin, Fauzi; Huda, Miftahul; Tambajong, Edgar Benedicth Yehezkiel; Sihombing, Dina Agnesia; Devgan (Institut of Shanti Bhuana, 2025)
TikTok is one of the most widely used social media platforms, featuring video-based content with durations ranging from 15 seconds to 10 minutes, providing interactive services for users of all demographics. Excessive use of TikTok can lead to negative effects, including potential impacts on an individual's academic performance. This study aims to analyze the influence of TikTok on users' academic achievement tendencies, providing insights into the impact of TikTok usage on academic performance and identifying necessary preventive measures to avoid excessive use of the application. Using a quantitative approach, data were collected through a questionnaire distributed via a TikTok account, and an analysis was conducted to analyze the correlation between TikTok usage and its impact on users' academic performance. The findings indicate that the correlation strength in this study is weak, as evidenced by a Pearson Correlation value of 0.204, suggesting that TikTok may be a minor contributing factor influencing users' academic performance.